The Responsibility of the Sub-District Head as a Temporary Land Deed Official in Making Deeds of Transfer of Land Rights: A Review in the Perspective of Positive Law and Islamic Law - Adha Hamzah, Yuli; Anggraeny Mangarengi, Arianty (Al-'Adl, 2025)
This research aims to examine and analyze the responsibilities of the Sub-district Head as the Temporary Land Deed Making Officer (PPATS) in making the deed of transfer of land rights, as well as to review its implementation from the perspective of positive law and Islamic law. The sub-district head who is given the authority as a Temporary PPATS has a legal responsibility in ensuring the validity of the deed made, both administratively and substantially. However, in practice, obstacles and inconsistencies are often found between implementation in the field and applicable normative provisions. This study uses an empirical legal approach with a qualitative descriptive method. Primary data was obtained through interviews with the Sub-district Head, officials of the National Land Agency (BPN), notaries/PPAT, community leaders, and Islamic legal experts. Meanwhile, secondary data is obtained through a study of laws and regulations, legal literature, and relevant fiqh books. Data analysis is carried out qualitatively through the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that the responsibility of the Sub-district Head as a Temporary PPATS has not been fully carried out optimally, especially in terms of mastery of the substance of agrarian law and understanding of the values of justice in Islamic law. From a positive legal perspective, the deed of transfer of rights made by the Sub-district Head has legal force as long as it meets the formal and material requirements. Meanwhile, from the perspective of Islamic law, the principles of justice, honesty, and agreement of the parties are the main basis in ownership transactions. Therefore, the synergy between positive legal rules and Islamic legal values needs to be improved to realize fair, transparent, and dignified land practices